DISCOURSE ANALYSIS OF DICTION USED IN “KUE DADING MANG OLEH” - Almizan Almizan; Didin Nuruddin Hidayat; Alek Alek (Universitas Muhammadiyah Kalimantan Timur, 2021)
The background of this research comes from the viral post of Mang Oleh’s homemade named Odading cake. Well-known uniquely reviewed by a man named Ade Londok. The controversial diction that is used by Ade Londok is very interesting, unusual, and of course, amusing. His entertaining figure with his unusual review style made this man from the city of Bandung go viral. Previously, it was well-known that Ade Londok was promoting a typical Bandung home made cake called Odading in an amusing manner. He promoted Odading with his mixed accents, between Sundanese and Indonesian. He also slips in a tickling rhyme so that it makes his figure interesting to be viral. The approach used in this research is critical discourse analysis that used a video of Ade Londok and the script of his speech as the source to collect the data. The findings show that the content used Abstract word, Special word, Popular word, and Jargon. It can be concluded as in its original, primary meaning, refers to writers’ or speakers’ distinctive vocabulary choices and style of expression.